Optimasi Sumber Daya Manusia Melalui Peramalan di Departemen Cutting Menggunakan Metode Double Moving Average pada PT Great Golden Indonesia - Dewi Shofiana Saputri; Muhamamad Choiru Zulfa; Gun Sudiryanto (Journal Industrial Engineering and Management (JUST-ME), 2026)
Manufacturing industries face challenges in balancing workforce capacity with fluctuating production demand. This imbalance leads to excessive overtime, decreased productivity, and increasing operational costs. This study aims to analyze workforce requirements in the Cutting Department of PT Great Golden Indonesia using the Double Moving Average (DMA) method and determine the most efficient workforce planning strategy. The research employed a quantitative approach using historical production demand data from 12 periods and work measurement through Stopwatch Time Study. The research stages included demand forecasting, standard time calculation, production capacity analysis, workforce requirement calculation, and operational cost evaluation. The results showed that the Double Moving Average method generated an increasing demand trend from 94,155 units in March 2026 to 158,822 units in February 2027. The standard production time was 3.513 minutes per unit with a standard output capacity of 137 units per day. Based on workforce requirement analysis, the optimal number of employees increased from 31 workers to 53 workers by February 2027. The full recruitment strategy resulted in a total cost of Rp1,388,436,993.93 and was considered more efficient compared to the combination of gradual recruitment and overtime strategy. The study indicates that the DMA method can support companies in preparing more effective and efficient workforce planning.